Ober eine Klasse der partiellen Differentialgleichungen - Neniškytė, E. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Е. К. Ненишките. Об одном классе решений дифференциальных уравнений в частных производных E. Neniškytė. Apie vieną diferencialinių lygčių su dalinėmis išvestinėmis sprendinių klasę